The Froman Peace Campaign: Pluralism in Judeo-Islamic Theology and Politics - Schvarcz, Benjamin (Politics and religion, 2022)
Despite intensive diplomatic efforts, achieving peace between the Palestinian and Israeli populations remains out of reach. This study investigates a recent campaign for religious peacebuilding, focusing on the political theology of Rabbi Menachem Froman and his fellow religious peacemakers, family members, and disciples. Froman's position is twofold: First, religion is necessary for resolving the Israeli-Palestinian conflict; and second, Israeli settlements should not be considered an obstacle to peace, but rather "the fingers of Israel's outstretched hand for peace." We argue that "the Froman peace campaign" advances pluralism in both Judeo-Islamic theology and politics. It constructs a synthetic theological view incorporating principles and rituals of both religions. Politically, it promotes a plan for two states in one united confederation. By comparing the peace campaign of Rabbi Froman with that of Rabbi Michael Melchior, another well-known peacemaker, this article contributes to a growing literature on the role of theology in religious peacebuilding